Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1973
DOI: 10.1021/ja00797a040
|View full text |Cite
|
Sign up to set email alerts
|

Substituent effects. III. Dissociation constants of .beta.-arylpropionic acids, .beta.-arylisovaleric acids, N-arylglycines, aryloxyacetic acids, N-aryl-.beta.-alanines, and some related systems

Abstract: Dissociation constants of reaction series ArXCH2COOH, with X = CH2, CMe2, NH, O, S, and NHCH2, have been measured in water and/or ethanol-water mixtures. Deviations from the Hammett equation are found for -M substituents in the para position. These deviations, expressed in free energy terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Jencks observed that the equilibrium transfer of acyl groups to substituted thiols or thiol anions is less sensitive to polar substituents 44. However, he did not account this to a relative poor transmission of electron‐withdrawing effect of the acyl group through sulfur compared to oxygen or nitrogen, since the “fall‐off” factors for transmission of substituent effects through X in the ionization of ArXCH 2 COOH in 50% ethanol are 0.51, 0.52, 0.38, and 0.33–0.39 for S, O, NH, and CH 2 respectively 59, 60. He proposed that the significant contribution of the resonance form 3c of thiol esters accounted for the small sensitivity to substituents on sulfur.…”
Section: Resultsmentioning
confidence: 99%
“…Jencks observed that the equilibrium transfer of acyl groups to substituted thiols or thiol anions is less sensitive to polar substituents 44. However, he did not account this to a relative poor transmission of electron‐withdrawing effect of the acyl group through sulfur compared to oxygen or nitrogen, since the “fall‐off” factors for transmission of substituent effects through X in the ionization of ArXCH 2 COOH in 50% ethanol are 0.51, 0.52, 0.38, and 0.33–0.39 for S, O, NH, and CH 2 respectively 59, 60. He proposed that the significant contribution of the resonance form 3c of thiol esters accounted for the small sensitivity to substituents on sulfur.…”
Section: Resultsmentioning
confidence: 99%
“…There is some information about the effect of p-NH 2 as a substituent in phenylacetic or phenylpropionic acid. From pK a values in aqueous ethanolic solutions the apparent sigma value of p-NH 2 is in the range of about 0.20 to 0.25 124,125 . (Corrections for zwitter-ion content have been applied by the authors concerned.)…”
Section: Electronic Effects Of the Amino Group And Related Groups mentioning
confidence: 99%
“…For the sake of uniformity 0 values for CR substituents have also been based on such systems. Wepster and colleagues 124,125 , however, have criticized the use of systems in which the substituent is 'insulated' by methylene groups from the reaction centre for its tendency to lead to slightly exalted values of 0 for CR substituents, i.e. the supposed insulation is not 100% effective.…”
Section: Acids Of the Type Ph−g−coohmentioning
confidence: 99%
“…-<NMNPA is a colorless oil and was collected at vapor temperature and pressure listed (mm Hg). tHoefnagel et aL.,1973. 'Bryson et at., 1963 …”
mentioning
confidence: 99%